Stimuli-responsive biphenyl-tripeptide supramolecular hydrogels as biomimetic extracellular matrix scaffolds for cartilage tissue engineering. (1st September 2021) - Li, Xing; Bian, Shaoquan; Zhao, Mingda; Han, Xiaowen; Liang, Jie; Wang, Kefeng; Jiang, Qing; Sun, Yong; Fan, Yujiang; Zhang, Xingdong
Abstract: Supramolecular hydrogel composed of aromatic short peptide gelator was an attractive biomaterial owing to its simple and convenient synthetic route, nano-fibrillar microstructure resembling natural collagen fibers and intelligent response to external stimulus. Herein, stimuli-responsive biphenyl-tripeptide supramolecular hydrogels was prepared to simulate extracellular matrix scaffolds by temperature switch, ion induction and pH switch. The amino acid arrangement substantially affected gelation behavior, only BPAA-βAFF and BPAA-FFβA could form nanostructured supramolecular hydrogels with 8-10 nm nanotubes or nanofibers by potential intermolecular hydrogen bond interactions and π-π stacking. The minimum gelation concentration (MGC) and maximum storage modulus were 0.4 mM (0.023 wt%) and around 8.2 KPa. The two supramolecular hydrogels could support adhesion and proliferation of L929 cells. Moreover, the BPAA-βAFF hydrogel promoted proliferation and ECM secretion of chondrocytes in vitro, and facilitate the phenotype maintenance of hyaline cartilage. All the results demonstrated that BPAA-βAFF hydrogel hold great potential application prospects in cartilage tissue engineering. Statement of Significance: Diphenylalanine was served as a core segment conjugating with 4-biphenylacetic acid (BPAA) to produce biphenyl-tripeptide compounds with transforming amino sequence, and multiple external stimuli was applied to study the gelation properties of the aromatic short peptide gelators. "FF" brick (phenylalanine-phenylalanine) was crucial for formation of fibrous supramolecular hydrogels. Meanwhile, the sequence of amino acids arrangement also had an essential effect on the gelation behavior. Optimal BPAA-βAFF with ultra-low minimum gelation concentration (0.4 mM, about 0.023 wt%) and similar microstructure to extracellular matrix (ECM) of nature cartilage tissue could promote the proliferation and ECM secretion of chondrocytes in vitro, and facilitate the formation of hyaline cartilage. Graphical abstract: Image, graphical abstract